Phase separation and chemistry evolution in Fe-rich Sm(CobalFe0.31Cu0.07Zr0.025)7.7 magnets: The effect of initial defect. (15th February 2023) - Li, Qiangfeng; Wang, Chao; Lin, Zhongchong; Wang, Lei; Xiao, Yufei; Zhang, Peng; Cao, Xingzhong; Fang, Yikun; Liao, Qingliang; Yang, Jinbo; Zhang, Yue; Zhu, Minggang; et al.
Abstract: The intrinsic coercivity of Fe-rich Sm2 Co17 -type permanent magnets is closely associated with the unique cellular microstructures. Usually, the continuous distribution of cell boundaries is destroyed in Fe-rich Sm2 Co17 -type magnets. Herein, a relatively high maximum energy product of about 32.7 MGOe and a nearly 300% increase in intrinsic coercivity are observed for Fe-rich Sm2 Co17 -type permanent magnets via regulating the initial defects to introduce numerous 1:5H precipitates nucleation sites. Synchrotron XRD and HR-TEM results reveal that the solution-treated Fe-rich Sm2 Co17 -type magnets consist of supersaturated 1:7H phase and a partial 2:17R phase. Furthermore, the solution-treated magnet with a lower fraction of 2:17R phase was found to have a higher density of initial defects through positron annihilation spectroscopy measurement. In the magnet with a higher density of initial defects, high density of defects-aggregated cell boundaries and high internal stress promote the precipitation of 1:5H phase. Moreover, the ordering transformation of 2:17R phase was facilized during aging treatment, and elements segregation was promoted. These results present a novel way in designing high-performance Fe-rich Sm2 Co17 -type magnets. Graphical abstract: Image, graphical abstract